Revisiting Wandeuki: Migration, Belonging, and The Negotiation of Korean National Identity in Contemporary South Korea - Arie Raditya (Green Publisher Indonesia, 2026)
South Korea has experienced significant demographic transformation due to increasing labor migration, international marriages, and the emergence of multicultural families, challenging the long-standing ideology of hanminjok, which defines Korean national identity through ethnic homogeneity. This transformation raises important questions regarding how migration, belonging, and national identity are represented and negotiated within contemporary Korean society. This study aimed to examine how Kim Ryeoryeong’s novel Wandeuki (2008) represents migration experiences, multicultural identities, and the changing meanings of Korean national belonging within the context of South Korea’s evolving social landscape. Employing a qualitative textual analysis approach, this study analyzed the novel through the perspectives of the sociology of literature, Stuart Hall’s theory of representation, and Homi K. Bhabha’s concept of hybridity. The findings revealed that Wandeuki functions as a cultural archive that captures the tensions between ethnic nationalism and multicultural realities. The analysis demonstrated that migrant figures in the novel represent various dimensions of migration experiences, including labor precarity, marriage migration, and mixed-heritage identities. Furthermore, the study showed that legal citizenship does not necessarily guarantee social acceptance, as cultural recognition remains influenced by ethnicity, language, and broader social perceptions. In conclusion, Wandeuki remains relevant as a literary text that reflects South Korea’s ongoing negotiation of national identity beyond ethnic homogeneity and highlights the need for broader understandings of belonging within an increasingly multicultural society.